A Straightforward Design and Implementation of Real Time Pressure Monitoring System in Water Pipe - Dwi Astharini; Arizka Arizka (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2014)
This paper reports the development of a real time system for pressure monitoring inside water pipe. In water supply industry it is valuable to know the water pressure inside the pipe. Thus the system created consisting hardware parts in compact form along with software in laptop for high mobility. In the hardware part, pressure gauge is chosen as sensor, and a conversion of the data into frequency is decided for better communication with the computer. The process in the software includes data captures, conversion, and display using visual basic MSviewer.